2021
DOI: 10.23947/2334-8496-2021-9-2-253-264
|View full text |Cite
|
Sign up to set email alerts
|

Features of Critical Thinking of Individual Entrepreneurs With Different Levels of Self-Regulation

Abstract: In the crisis conditions of entrepreneurs business functioning in Russian, it is important to develop critical thinking in conjunction with the skills of self-regulation of behavior. It is assumed that entrepreneurs with different styles of self-regulation differ in the level of critical thinking, and there is also a relationship between the styles of self-regulation and the level of critical thinking. The theoretical basis of the study is the idea of the relationship between the degree of formation of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…In this context, it can be said that primary school students' critical thinking dispositions affect their entrepreneurial tendencies at a high level and positively. According to Molokhina et al (2021), there is a confirmation of two hypotheses of their research work about the existence of features of the development of critical thinking in individual entrepreneurs with different styles of self-regulation and the relationship between the styles of self-regulation and the features of critical thinking. The lack of internal freedom and the ability to think critically can cause the individual entrepreneur to depend on the circumstances and engage in ineffective behavior.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…In this context, it can be said that primary school students' critical thinking dispositions affect their entrepreneurial tendencies at a high level and positively. According to Molokhina et al (2021), there is a confirmation of two hypotheses of their research work about the existence of features of the development of critical thinking in individual entrepreneurs with different styles of self-regulation and the relationship between the styles of self-regulation and the features of critical thinking. The lack of internal freedom and the ability to think critically can cause the individual entrepreneur to depend on the circumstances and engage in ineffective behavior.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…The modern multimodal learning strategy is considered by a part of the professional community that develops the problems of generational change, issues of education and developmental psychology. So, for example, V. Pishchik, N. Sivrikova and others in a number of empirical studies have revealed significant differences between representatives of generations in terms of measured indicators [1][2][3][4]. These researchers often use a generational approach to characterize the subjects of the modern educational environment in which a multimodal learning strategy is integrated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This indicated that collaborative decision-making skills were needed in the industrial era 4.0 (Torres, Pimentel and Matias, 2023). The methodological competencies were also selected as essential and relevant characteristics for physics careers (Nasri, Nasri and Talib, 2020), with decision-making skills closely related to the abilities of critical thinking (Molokhina, Pishchik and Fomin, 2021) and communication (Tsai et al, 2020). Therefore, schools need to promote decision-making skills through classroom learning.…”
Section: Introductionmentioning
confidence: 99%